A new surface structural approach to ion adsorption: Tracing the location of electrolyte ions - Rahnemaie, Rasoul; Hiemstra, Tjisse; van Riemsdijk, Willem H. (Journal of colloid and interface science, 2006)
Electrolyte ions differ in size leading to the possibility that the distance of closest approach to a charged surface differs for different ions. So far, ions bound as outersphere complexes have been treated as point charges present at one or two electrostatic plane(s). However, in a multicomponent system, each electrolyte ion may have its own distance of approach and corresponding electrostatic plane with an ion-specific capacitance. It is preferable to make the capacitance of the compact part of the double layer a general characteristic of the solid–solution interface. A new surface structural approach is presented that may account for variation in size of electrolyte ions. In this approach, the location of the charge of the outersphere surface complexes is described using the concept of charge distribution in which the ion charge is allowed to be distributed over two electrostatic planes. It was shown that the concept can successfully describe the pH dependent proton binding and the shift in the isoelectric point (IEP) in the presence of variety of monovalent electrolyte ions, including Li +, Na +, K +, Cs +, Cl −, NO − 3, and ClO − 4 with a common set of parameters. The new concept also sheds more light on the degree of hydration of the ions when present as outersphere complexes. Interpretation of the charge distribution values obtained shows that Cl − ions are located relatively close to the surface. The large alkali ions K +, Cs +, and Rb + are at the largest distance. Li +, Na +, NO − 3, and ClO − 4 are present at intermediate positions.